An Evaluation of CSR Areas in Influencing Mobile Phone Purchasing Intention by Customers in Malaysia - Han, Xi (2014)
Problem: Corporate social responsibility shows frequently in various kinds of reports of different companies. However, managers are confused about how to practice CSR strategically. Little is known about consumers’ awareness of CSR and how consumers react toward socially responsible corporations and their products. The mobile phone retail industries have been criticized a lot on CSR because of unethical and unsustainable business activities. Some famous companies in the mobile phone retail companies are focusing on different CSR practices; however the research on CSR and its impact on consumer behavior in mobile phone companies still limited in Malaysia. It is critical importance to conduct the research on consumers’ awareness of CSR and to explore consumers’ attitudes and tendency of purchase behavior toward CSR in the mobile retail industry. Research purpose: The purpose of this thesis is to conduct an investigation about consumers’ awareness of CSR in the mobile phone industry. Furthermore, the aim is to investigate consumers’ attitudes on different CSR activities and how consumers’ purchasing behaviors are affected by these CSR activities. Theoretical perspective: This study combines stakeholder theory with theory on CSR’s impact on consumers’ attitudes and behavior. It refers to consumers as one important stakeholder group for a company. Design/methodology/approach: A quantitative method is used in this research. Primary data of consumers’ awareness of CSR, consumers’ attitudes and tendency of purchasing behavior were collected through a face to face questionnaire. The results of the questionnaire were analyzed and interpreted. Conclusions: The conclusions of this research are mobile phone customers do care about CSR and they regard CSR practices is important to the mobile phone companies. And according to the analysis results, customers are more care about whether companies taken responsibility to their employees.